Pemanfaatan Asap Cair Sabut Kelapa Sebagai Bahan Koagulasi Lateks - Dewi, Hesti Hertika Sari; Maryanti, Maryanti; Delvitasari, Febrina (Politeknik Negeri Lampung, 2019)
Smoke liquid for latex coagulant is one of the solution to avoid the negative impact of not recomended coagulant such as vinegar, TSP fertilizer and alum. Coconut fiber has lignin content so that it can be processed into liquid smoke. The aim of this study was to determination the best dose of coconut fiber liquid smoke for latex coagulant and the effect on the quality of SIR product. The treatment used in this study was the dose of coconut coir liquid smoke (formic acid (control) 4.76% v/v, 13.04% v/v, 14.89% v/v, 16.67% v/v, 18 v/v, 36% v/v, and 20% v/v). The results showed that the coconut fiber liquid smoke with dose 20% v/v gave the best result on time for clumping latex, total coagulum and total rubber yield. Based on quality data, a dose of 20% v/v include SIR 20 quality.